CAPACITY BUILDING AND POVERTY REDUCTION AMONG RURAL WOMEN IN IDEATO SOUTH LGA, IN IMO STATE, NIGERIA - Emeto, Milicent; Osita-Njoku, Agnes; Okechukwu Iwu, Uchenna (African Journal of Social and Behavioural Sciences, 2025)
This study investigated the impact of capacity building and poverty reduction among rural women in Ideato South LGA, Imo State, Nigeria, with a particular focus on tailoring programs. The research aimed to examine whether women’s empowerment through tailoring led to financial independence, whether government-provided credit incentives improved living standards, and the extent to which skills acquisition programs reduced economic backwardness. The study adopted a survey research design, with a sample of 325 respondents selected using simple random and purposive sampling techniques. The data collected were analysed using descriptive statistics and Chi-square tests to test the study’s hypotheses. The results revealed a significant relationship between women’s empowerment through tailoring and financial independence (χ² = 7.9, p < 0.05). Furthermore, the provision of government credit incentives was found to significantly enhance the standard of living of rural women (χ² = 8.3, p < 0.05). Lastly, skills acquisition programs, particularly in tailoring, were shown to have significantly reduced economic backwardness among rural women (χ² = 6.4, p < 0.05). These findings suggested that capacity-building initiatives, such as tailoring programs, played a crucial role in empowering rural women and improving their socio-economic conditions.